Analisis Perbandingan Pemberian Pupuk Organik Cair Dan Pupuk Kimia Cair Terhadap Pertumbuhan Tanaman Sawi Dengan Sistem Hidroponik - Filtar, Muhammad; Ridwan (Jurnal Sains dan Pendidikan Biologi, 2023)
Hydroponic cultivation is very popular throughout the world due to efficient resource management and quality food production. This research aims to compare the use of liquid organic fertilizer with liquid chemical fertilizer (AB Mix) on the growth of mustard greens in a hydroponic system. The research used a Randomized Block Design with 2 treatments and three replications. The research stages include: preparation of tools and materials, preparation of the hydropic building, making liquid organic fertilizer, sowing and planting, measuring plant height, number of leaves, leaf length and leaf width. The results of the research showed that the application of liquid organic fertilizer and liquid chemical fertilizer did not have a significant difference in the growth of mustard greens, both in the growth of plant height, leaf width, leaf length and leaf width